Health system decentralization in Venezuela during the 1990s (2011)
This paper is a short view of the Decentralisation to the Regional Health Systems in Venezuela during the decade of the 1990s, and it is based on my doctoral dissertation. It begins with some theoretical and conceptual foundations used in the thesis. Second, the paper shows the analytical framework for the “policy trajectory” followed by the decentralisation process examined in the research. In a third section, some comments on the main findings with regard to the institutional outcomes are analysed, but details are no illustrated here. Section 4 is a review of the political and policy process factors conditioning the decentralisation process. Sections 5 and 6 analysed how the changes in the Venezuelan rules of the game impacted on decision rights and spaces in the Regional Health Systems. Finally, some concluding remarks are show.